The term Old Maghreb; In light of the conflict of defining population origins, controlling geographical boundaries, and their relationship to naming sociohistorica study - SOULIM, Samira; MIDAR, Abdelouahabe (Social Sciences Journal, 2023)
In this study, we will try to talk about the old lobby society in its general concept, which inhabited the area confined between the West Nile to the Atlantic Ocean, where the name “Lobby” spread from that idiomatic designation in the classical sources stemming from the concept of “Luba” or “Lubia” among the Greek historians and geographers. who considered it refers to the entire north of the African continent. The Egyptian inscriptions dating back to the first millennium BC are the first and most important historical documents that constitute a basic source that tells us about the general features of the tribes of the ancient Maghreb; Which was In this study, we will try to talk about the inhabitants of the ancient Maghreb, as the Egyptian texts are the first and most important historical documents that constitute a basic source that tells us about the general features of the tribes of the ancient Maghreb, which were known by famous names in the hieroglyphic texts, namely the tribes of Tahnu and Tammoh and then the Libyan and Mushawash, that the largest These groups are known as the Libo tribes, whose influence extended to most of North Africa. This name was the first to be mentioned in the hieroglyphic inscriptions. Therefore, the ancient lobbies referred to by archaeological and historical sources are not confined to the West Nile region, but rather mean the inhabitants of the ancient Maghreb since the second millennium BC. birth